Use of environmental product declarations (EPDs) of pavement materials in the United States of America (U.S.A.) to ensure environmental impact reductions. (10th February 2021) - Rangelov, Milena; Dylla, Heather; Mukherjee, Amlan; Sivaneswaran, Nadarajah
Abstract: Recent green public procurement (GPP) initiatives in the U.S.A. rely on the use of the construction materials EPDs. EPD programs, however, were initiated by the material manufacturers, motivated by their interest to use EPDs as communication tools, improve production efficiency, and extend outreach. The goal of GPP initiatives is to produce the environmental improvements, however, it is unclear if the current EPD programs and GPP mechanisms can reliably support that goal. This study investigates the use of EPDs in GPP to ensure the environmental improvement of materials (use of EPDs as a procurement aid) and pavements (use of EPDs as a data source). The objective of this study was to identify prerequisites, challenges, implementation frameworks that include stakeholders and ensure environmental benefits with EPDs. A review of to-date EPD programs for pavement materials, communication with stakeholders, and analysis of pavement life cycle assessment (LCA) were performed. The use of EPDs that ensures environmental improvements of materials is contingent on EPD consistency and PCR prescriptiveness. EPDs can be suitable as data sources in pavement LCA due to their availability, transparency, and because they facilitate collaboration and improvements throughout the supply chain. However, it is noteworthy that if EPDs are used in that capacity, harmonization of all relevant PCRs and the establishment of aligned pavement LCA framework are necessary for reliable environmental improvements. The availability of public background data can support both EPD development and GPP efforts, by providing transparency, inclusivity, and low costs of LCA. Greater automation, systems for data transfer and management, and increased stakeholder collaboration can also support GPP in a way that ensures environmental improvements of pavement materials and infrastructure. Highlights: EPD programs of pavement materials were reviewed for their suitability in GPP. Frameworks for EPD use to ensure environmental reductions were developed. PCR prescriptiveness and harmonization provide consistency and reliability of EPDs. Public background databases with regular updates can support GPP goals.